Konstruksi Sosial Gender pada Profesi Penata Kuku - Satriantoro, Herald Faisal; Alfadri, Bayu; Marcello, Zuniro; Musa, Dahniar Th.; Alamri, Annisa Rizqa (Universitas Cenderawasih, 2023)
This article aims to uncover the realities of the social construction of gender surrounding the profession of nail stylist in Pontianak City. It explores the stereotypes and stigmas associated with individuals working in the nail care industry, particularly for men in their field of profession. This research refers to the social construction of gender theory proposed by Peter L. Berger and Thomas Luckmann, using an anthropological lens to examine gender and sexuality, with a focus on the characteristics and stigmas associated with being a nail technician. This research adopts a qualitative approach, employing a case study method in Pontianak City, supported by unstructured interviews, secondary data, and available research documents from the internet. The findings of this research challenge the social construction that declares nail care as suitable only for women and that only effeminate men are suitable for this profession, contrasting with the reality found through the accounts of the informants.